A multi-channel biotelemetry system for the acquisition and processing of respiratory sounds - Çiftçi, Rifat Koray. (Thesis (M.S.) - Bogazici University. Institute of Biomedical Engineering, 2001., 2001)
Respiratory disorders can be diagnosed by analyzing respiratory sounds produced during breathing. Main tool for physicians to analyze respiratory sounds is stethoscope. Developing a system capable of acquiring and displaying respiratory sounds and performing real-time analysis and classification is a challenging goal for researchers.This study presents a preliminary approach for the telemetry of respiratory sounds. Increasing the reliability and efficiency of the acquisition process of respiratory sounds is aimed. For this purpose, a system with two separate telemetry transmitters placed on the body of the patient and a remote receiver connected to a PC is developed. A radio frequency link is established between the transmitters and the receiver using frequency modulation.Communication between the PC and receiver is supplied via serial port. To control data acquisition process, a user interface is developed. The receiver can be tuned to any of the transmitters with the help of this interface, which provides the user with the choices of listening, recording and displaying data. A microcontroller is responsible for tuning the receiver according to the commands issued by the computer. The respiratory sounds are filtered by high pass and low pass filters having cut-off frequencies at 80 Hz and 2000 Hz, respectively. A sampling frequency of 5 kHz is selected. Data is digitized by an 8-bit analog-to-digital converter.Performance of the system is tested by measuring its response to some pre-defined signals and by recording respiratory sounds from human subjects. Promising results are obtained revealing the feasibility of telemetering respiratory sounds.
Keywords: Respiratory organs -- Sounds.; Biotelemetry.; Radio frequency modulation.